Identifying SYNE1 Ataxia With Novel Mutations in a Chinese Population - Peng, Yun; Ye, Wei; Chen, Zhao; Peng, Huirong; Wang, Puzhi; Hou, Xuan; Wang, Chunrong; Zhou, Xin; Hou, Xiaocan; Li, Tianjiao; Qiu, Rong; Hu, Zhengmao; et al. (Frontiers in Neurology, 2018)
Objective: Variants in SYNE1 have been widely reported in ataxia patients in Europe, with highly variable clinical phenotype. Till now, no mutation of SYNE1 ataxia has been reported among the Chinese population. Our aim was to screen for SYNE1 ataxia patients in China and extend the clinicogenetic spectrum. Methods: Variants in SYNE1 were detected by high-throughput sequencing on a cohort of 126 unrelated index patients with unexplained autosomal recessive or sporadic ataxia. Pathogenicity assessments of SYNE1 variants were interpreted according to the ACMG guidelines. Potential pathogenic variants were confirmed by Sanger sequencing. Clinical assessments were conducted by two experienced neurologists. Results: Two Chinese families with variable ataxia syndrome were identified (accounting for 1.6%; 2/126), separately caused by the novel homozygous SYNE1 mutation (NM_033071.3:c.21568C>T, p.Arg7190Ter), and compound heterozygous SYNE1 mutation (NM_033071.3: c.18684G>A, p.Trp6228Ter; c.17944C>T, p.Arg5982Ter), characterized by motor neuron impairment, mental retardation and arthrogryposis. Conclusions: SYNE1 ataxia exists in the Chinese population, as a rare form of autosomal recessive ataxia, with a complex phenotype. Our findings expanded the ethnic, phenotypic and genetic diversity of SYNE1 ataxia.